2020
DOI: 10.1101/2020.09.10.291062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FMRP sustains presynaptic function via control of activity-dependent bulk endocytosis

Abstract: Synaptic vesicle (SV) recycling is essential for the maintenance of neurotransmission, with a number of neurodevelopmental disorders linked to defects in this process. Fragile X syndrome (FXS) results from a loss of fragile X mental retardation protein (FMRP) encoded by the FMR1 gene. FMRP is an established translation repressor, however it also has translation-independent presynaptic roles, including regulation of the trafficking and function of specific ion channels. Since defects in SV recycling are exacerb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…4e-k). Recently, it was reported that the FMRP-R138Q mutant fails to restore activity-dependent bulk endocytosis (ADBE) in Fmr1-KO neurons, perhaps through the loss of BK channel interaction 32 . Our EM measurements also revealed a significant increase in the density of presynaptic vesicles in Fmr1 R138Q hippocampal termini (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4e-k). Recently, it was reported that the FMRP-R138Q mutant fails to restore activity-dependent bulk endocytosis (ADBE) in Fmr1-KO neurons, perhaps through the loss of BK channel interaction 32 . Our EM measurements also revealed a significant increase in the density of presynaptic vesicles in Fmr1 R138Q hippocampal termini (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fmr1 KO neurons also display alterations in the size of functional SV pools (Deng et al, 2011;Klemmer et al, 2011;Bonnycastle et al 2020). This may reflect compensation for reduced activity-dependent bulk endocytosis (Bonnycastle et al 2020), a mode of endocytosis only triggered during periods of elevated neuronal activity (Kokotos & Cousin, 2015). However, altered SV pool sizes are unlikely to contribute to spontaneous SV fusion, since no increase in action potential-driven SV fusion was observed in Fmr1 KO neurons, in agreement with (Bonnycastle et al 2020).…”
Section: Increased Spontaneous Sv Fusion In Fmr1 Ko Neurons Depends On Spontaneous Activitymentioning
confidence: 88%
“…It also regulates both the density and localization of N-type calcium channels (Ca V 2.2) in dorsal root ganglion (DRG) cells (Ferron et al, 2014(Ferron et al, , 2020. Fmr1 KO neurons also display alterations in the size of functional SV pools (Deng et al, 2011;Klemmer et al, 2011;Bonnycastle et al 2020). This may reflect compensation for reduced activity-dependent bulk endocytosis (Bonnycastle et al 2020), a mode of endocytosis only triggered during periods of elevated neuronal activity (Kokotos & Cousin, 2015).…”
Section: Increased Spontaneous Sv Fusion In Fmr1 Ko Neurons Depends On Spontaneous Activitymentioning
confidence: 99%